2015
DOI: 10.7717/peerj.971
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miR-194-5p as a potential biomarker for postmenopausal osteoporosis

Abstract: The incidence of osteoporosis is high in postmenopausal women due to altered estrogen levels and continuous calcium loss that occurs with aging. Recent studies have shown that microRNAs (miRNAs) are involved in the development of osteoporosis. These miRNAs may be used as potential biomarkers to identify women at a high risk for developing the disease. In this study, whole blood samples were collected from 48 postmenopausal Chinese women with osteopenia or osteoporosis and pooled into six groups according to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 39 publications
2
59
0
4
Order By: Relevance
“…This miRNA was repressed in BmOvx group and not modulated in calvaria osteoblastic cells, suggesting its influence in decreasing bone marrow osteoblastic cell differentiation in ovariectomized animals. Finally, the upregulation of miR-194-5p in bone marrow osteoblastic cells from ovariectomized rats is in agreement with other investigations (Meng et al, 2015), who showed their remarkably higher expression in the peripheral blood of patients with osteoporosis compared to that observed in the blood of patients with osteopenia, suggesting that this miRNA might be suitable as potential biomarker for postmenopausal osteoporosis.…”
Section: Discussionsupporting
confidence: 92%
“…This miRNA was repressed in BmOvx group and not modulated in calvaria osteoblastic cells, suggesting its influence in decreasing bone marrow osteoblastic cell differentiation in ovariectomized animals. Finally, the upregulation of miR-194-5p in bone marrow osteoblastic cells from ovariectomized rats is in agreement with other investigations (Meng et al, 2015), who showed their remarkably higher expression in the peripheral blood of patients with osteoporosis compared to that observed in the blood of patients with osteopenia, suggesting that this miRNA might be suitable as potential biomarker for postmenopausal osteoporosis.…”
Section: Discussionsupporting
confidence: 92%
“…The same group identified another miRNA in circulating monocytes, miR-422a, as a potential biomarker for postmenopausal osteoporosis [13]. More recently, 5 dysregulated miRNAs in osteosarcoma were identified in microarray analysis and upon further subjection to pathway analysis only miR-194-5p was enriched in osteoporosis related pathways suggesting miR-194-5p as a potential biomarker for postmenopausal osteoporosis [11].…”
Section: Discussionmentioning
confidence: 98%
“…A most recent study identified a range of dysregulated miRNAs in osteoporosis related pathways and suggests miR-194-5p as a viable biomarker for postmenopausal osteoporosis [11]. Similarly, miR133a and miR422a have been identified as potential biomarkers for postmenopausal osteoporosis [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-194 has been identified as a prognostic marker of clear cell renal cell carcinoma (ccRCC) [19], myelodysplastic syndromes (MDS) [20], and HCC [15]. In addition to cancers, the biological functions of miR-194 in other diseases such as diabetes [21] and postmenopausal osteoporosis have also been investigated [22]. More recently, a study demonstrated that miR-194 was related with inflammatory response induced by palmitic acid (PA) [23].…”
Section: Discussionmentioning
confidence: 99%